Katharine Hepburn s’en va-t-en guerre / Katharine Hepburn goes to war - Jules SANDEAU (E-REA)
This article focuses on a relatively unstudied period of Hepburn’s career, which corresponds to the US participation in the Second World War. It analyses the way in which the films Woman of the Year (1942), Keeper of the Flame (1943), Dragon Seed (1944) and Without Love (1945) shape the star’s image in order to adapt it to their specific socio-historical context. It does so by also examining the promotional material surrounding the films releases and by focalizing on the gender dimension of Hepburn’s persona. While underlining the ambivalence of these films, this study highlights the way in which the star’s deviations from gender norms were relatively and momentarily valued as assets used in the national interest.